The NAC proton treatment planning system - Schreuder, Andries N.; Schlegel, Wolfgang; Höss, Angelika (Strahlentherapie und Onkologie, 1999)
Summary: A three-dimensional proton treatment planning system called PROXELPLAN has been used at the National Accelerator Centre (NAC) since October 1994. This system is entirely based on the VOXELPLAN planning system, developed at the Deutches Krebsforschungszentrum (DKFZ), Heidelberg, Germany. The VOXELPLAN system provides the treatment planning infrastructure while the proton dose distributions are calculated using a software module that was initially developed at the Royal Marsden Hospital, UK. The proton module has been extensively modified and refined. It uses a rayline-tracing algorithm which is suitable for planning current treatments but is not sufficiently dynamic to accommodate the use of compensators. A sophisticated pencil beam algorithm is currently under development.